From Socioenvironmental Inequality to Sustainable Development: The Case of Cantinho do Céu - Silva, Laura Dallabrida Leite e; Ferreira, Letícia Tamisari; França, Elisabete (MAJ - Malaysia Architectural Journal, 2025)
The present article showcases the case of Cantinho do Céu, a territory that, through well-structured public policies and interdisciplinary planning, has emerged as an exemplary instance of successful intervention in unplanned settlements within peripheral and environmentally fragile areas. Situated in the southern zone of São Paulo, Brazil, Cantinho do Céu is a peninsula within a watershed area along the shores of the Billings Reservoir. The occupation of the area occurred as a consequence of the city's rapid and unplanned expansion, through the opening of irregular subdivisions that deforested almost the entire original Atlantic Forest and did not adhere to land parceling regulations in force at the time. The houses, constructed through self-building, came to shelter approximately 10,400 families without access to basic infrastructure, which, in 2010, characterized Cantinho do Céu as one of the largest precarious settlements in the largest metropolis in Latin America; located, as an aggravating factor, in an environmental protection area. This study aims to explore the challenges of articulating social and environmental issues faced by the municipality of São Paulo in developing plans and projects for interventions in socially fragile and environmentally protected areas. Overcoming orthodox planning practices and through interdisciplinary collaboration across various spheres of the public sector, the program structured simultaneous intervention strategies that qualify the occupation without altering the urban fabric or existing housing, while also implementing sanitation and drainage systems, eliminating risk areas, and creating green spaces and public areas. Thus, the case of Cantinho do Céu exemplifies how it is possible for the public sector to promote sustainable development in irregular settlements, respecting local aesthetics and culture, celebrating urban plurality, and simultaneously preserving the environment.